Pengaruh Kosmologi Bumi, Matahari, dan Bulan Terhadap Ritual Kepercayaan Masyarakat Jawa Tentang Gerhana di Era Kontemporer - Rizqita Ghina Fawziya Nurherizza; Nanang Saptono (PANALUNGTIK, 2024)
The concept of cosmology already exists in the knowledge system in human culture. The universe consists of the macrocosm and microcosm understood by the Indonesian people since prehistoric times and developed during the entry of Hindu-Buddhist culture. One of the natural phenomena that is very closely related to the culture of the Indonesian people is the eclipse. Events give birth to traditions in people's lives in the form of knowledge systems and rites. This study aims to find out how the conception of cosmological is understood by the public. Furthermore, more specifically, it explains how eclipse events are understood and addressed by the Javanese people in the form of a system of knowledge and rites. The research method applies the descriptive type through qualitative methods. Data collection through literature studies. The results of the study show that the concept of cosmology in Javanese culture has been known since the entry of Hindu-Buddhist culture and developed under the influence of Islamic culture. The eclipse phenomenon is understood to be a marker of disaster. To avoid disasters, certain rituals are carried out.